Neonatal Life Support 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. (November 2020) - Wyckoff, Myra H.; Wyllie, Jonathan; Aziz, Khalid; de Almeida, Maria Fernanda; Fabres, Jorge W.; Fawke, Joe; Guinsburg, Ruth; Hosono, Shigeharu; Isayama, Tetsuya; Kapadia, Vishal S.; Kim, Han-Suk; Liley, Helen G.; et al.
Abstract: This 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations (CoSTR) for neonatal life support includes evidence from 7 systematic reviews, 3 scoping reviews, and 12 evidence updates. The Neonatal Life Support Task Force generally determined by consensus the type of evidence evaluation to perform; the topics for the evidence updates followed consultation with International Liaison Committee on Resuscitation member resuscitation councils. The 2020 CoSTRs for neonatal life support are published either as new statements or, if appropriate, reiterations of existing statements when the task force found they remained valid. Evidence review topics of particular interest include the use of suction in the presence of both clear and meconium-stained amniotic fluid, sustained inflations for initiation of positive-pressure ventilation, initial oxygen concentrations for initiation of resuscitation in both preterm and term infants, use of epinephrine (adrenaline) when ventilation and compressions fail to stabilize the newborn infant, appropriate routes of drug delivery during resuscitation, and consideration of when it is appropriate to redirect resuscitation efforts after significant efforts have failed. All sections of the Neonatal Resuscitation Algorithm are addressed, from preparation through to postresuscitation care. This document now forms the basis for ongoing evidence evaluation and reevaluation, which will be triggered as further evidence is published. Over 140 million babies are born annually worldwide (https://ourworldindata.org/grapher/births-and-deaths-projected-to-2100 ). If up to 5% receive positive-pressure ventilation, this evidence evaluation is relevant to more than 7 million newborn infants every year. However, in terms of early care of the newborn infant, some of the topics addressed are relevant to every single baby born.